2018
DOI: 10.1371/journal.pone.0206488
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a HPLC/FLD method combined with online derivatization for the simple and simultaneous determination of trace amino acids and alkyl amines in continental and marine aerosols

Abstract: A method was developed for simultaneous determination of 15 amino acids and 7 alkyl amines. The method was based on the employment of high performance liquid chromatography/fluorescence detection and online derivatization with o-phthaldiadehyde. The 22 derivatives were separated within 30 min including the equilibration time and detected by a fluorescence detector at an excitation wavelength of 230 nm and emission wavelength of 450 nm. The analysis procedure was satisfactorily validated by the reproducibility,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 46 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Many studies have been conducted on the gaseous and particulate amines over the East China Sea and the adjacent continents. Huang et al (2018) found that monomethylamine (MMA) is the dominant particulate amine in the East China Sea, ranging from 0.27 to 7.04 ng m −3 with an average of 4.76 ng m −3 . High concentrations of particulate DMA and particulate TMA + DEA were found in the East China Sea, ranging from 30.2 to 32.2 and 11.8 to 27.5 ng m −3 , respectively (Xie et al, 2018; Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted on the gaseous and particulate amines over the East China Sea and the adjacent continents. Huang et al (2018) found that monomethylamine (MMA) is the dominant particulate amine in the East China Sea, ranging from 0.27 to 7.04 ng m −3 with an average of 4.76 ng m −3 . High concentrations of particulate DMA and particulate TMA + DEA were found in the East China Sea, ranging from 30.2 to 32.2 and 11.8 to 27.5 ng m −3 , respectively (Xie et al, 2018; Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Amine emissions also vary in different coastal areas. The concentration of aerosol amines in Shanghai was lower than that of Huaniao Island, 83 while it was approximately 4-fold higher than that on an isolated coast of Chongming Island. 78 Similar to coastal areas, forest areas also show different pollution characteristics of atmospheric amines.…”
Section: Temporal and Spatial Distribution Characteristics Of Atmosph...mentioning
confidence: 70%